The impact of climate risk on corporate credit risk - Francesca Bell; Gary Van Vuuren (Cogent Economics & Finance, 2022)
Firms must estimate expected credit losses (EL) to comply with accounting standards and unexpected credit losses (UL) to determine regulatory credit risk capital. Both rely on estimates of obligor probabilities of default (PD). Investors also pay close attention to credit ratings-derived from inter alia default rates. Changes in climate will increase firm default rates. Studies investigating the impact of climate change on PDs are limited because this is a novel field and data are still relatively scarce. Africa will be most severely impacted by climate change: default rates will deteriorate leading to increased PDs, LGDs, provision requirements (through increased expected losses) and regulatory credit risk capital (through increased unexpected losses). Corporate equity prices are simulated using Geometric Brownian motion (GBM) and shocks brought about by climate events of differing frequency and severity are applied to these simulated prices. Post shock prices and return volatilities are differentially affected depending on the nature of the applied shock. These constitute inputs into a well-known model of corporate default form which resultant PDs may be extracted. A possible calibration approach is developed for climate event-based impacts on corporate default rates. A scaling factor matrix (an amount by which the unaffected default rate increases after a specified climate event type occurs) can help market participants forecast default rate changes. Climate related impacts have been quantified, calibrated, and used to assess credit quality degradation.
Keywords: D62; G11; G12; G23; M14; Q5; 330; Climate risk; forward looking; GBM; KMV; LGD; PD